2022
DOI: 10.1111/rmir.12203
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the InsurTech dynamics in the transformation of the insurance sector

Abstract: InsurTechs have transformed the insurance sector by becoming a fundamental role in leveraging technology to respond to business and costumers needs, driving solutions based on the availability of new data sources, the interconnectivity among actors, or even access to new possibilities in terms of risk hedging. InsurTechs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 17 publications
0
16
0
2
Order By: Relevance
“…Pursuing the above argument, previous research findings (Sosa & Montes, 2022) have identified five InsurTech driving capabilities that have been instrumental in boosting innovations in the insurance sector. According to what has driven InsurTech, these capabilities suggest 15 innovations transforming the insurance sector.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Pursuing the above argument, previous research findings (Sosa & Montes, 2022) have identified five InsurTech driving capabilities that have been instrumental in boosting innovations in the insurance sector. According to what has driven InsurTech, these capabilities suggest 15 innovations transforming the insurance sector.…”
Section: Discussionmentioning
confidence: 91%
“…On the other hand, the pace of technological change in the last decade has been exponential (Catlin & Lorenz, 2017; Lee & Shin, 2018) in a sector that is being boosted by technology (Cappiello, 2020), which is driving the fundamental transformation of the insurance industry by having a new way of interaction between insurers and customers, digitizing and automating business processes and creating new products (Eling & Lehmann, 2018). For both reasons, InsurTechs should be seen as technology‐driven innovations coinciding that have disrupted, accelerated, and enhanced the transformation of the insurance sector from the traditional structure leading to a dynamic user‐centric ecosystem (Sosa & Montes, 2022). Nevertheless, what is noteworthy is that, despite the agreement among scholars on the significant impact that Insurtechs are achieving in the insurance sector, the academic literature still needs to establish a consensus definition of InsurTech.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 3 more Smart Citations